Niobium Pentachloride Mediated (Hetero)aromatic Aldehyde Friedel–Crafts Hydroxyalkylation with Arenes: An Efficient Strategy to Synthesize Triarylmethanes - Rodrigues, Shirley M. M.; Previdi, Daniel; Baviera, Giovanni S.; Matias, Alexandre A.; Donate, Paulo M. (Synthesis, 2019)
Niobium pentachloride is an efficient and useful Lewis acid to conduct Friedel–Crafts hydroxyalkylation between arenes and (hetero)aromatic aldehydes, to generate triarylmethanes. This practical methodology offers several advantages, such as short reaction time, mild experimental conditions, and excellent yields.
Keywords: triarylmethanes; niobium pentachloride; Friedel–Crafts hydroxyalkylation; carbocations; (hetero)aromatic aldehydes